Widening the malt barley cultivation in north western plains of India - Verma, Ramesh Pal Singh; Kumar, Vishnu; Kharub, Ajit Singh; Kumar, Dinesh; Selvakumar, Rajan (Journal of Cereal Research, 2013)
DWRB73 and DWRUB 64, both are early maturing malt barley varieties with duration of 113 days (110-118 days) and 116 days (116-117 days), respectively. In malting quality analysis, DWRB 73 has shown good overall quality score (15/27) comparable to the best check DWRUB 52 (16/27) and superior to checks viz. RD 2668 (13/27) andK 551 (12/27). DWRUB 64 had better hectiolitre weight (59.20 kg), proportion of bold grains (87.5 %), hot water extract (77.1 % db), malt yield (88.9 %) and wort filtration rate (210.5 ml/hr) over the six-rowed check K 551, under late sown conditions.